APPLICATION OF EFFECTIVE AZIMUTH DIFFERENT FORMULA IN DETERMINING THE QIBLA DIRECTION - Ahmad, Auzi'ni Syukron Kamal; Shabir, Muslich (Al-Hilal: Journal of Islamic Astronomy, 2022)
The sun's shadow and the Qibla azimuth are two techniques for figuring out the Qibla direction. To obtain Qibla direction accuracy while applied to traditional instruments with low accuracy, such istiwa'ayn, the user's accuracy is required. Slamet Hambali's theory of a process angle was inspired by this issue. The effective angle disparity formula, which is based on Slamet Hambali's concept, is discussed in this article along with how it can be used to get effective azimuth variance. This article is based on numerically-based quantitative research using library data. The aim is to comprehend the concept of various effective azimuths and how they are used to identify the direction of the Qibla. This article comes to the conclusion that Slamet Hambali's formula for the effective azimuth difference tends to make use of the idea of processing angle by calculating the azimuth difference value with particular aiming hours, azimuth difference value, and processing angle to produce a shooting clock with a different azimuth valuation.Kata kunci : azimut, efektif, jam bidik